2015
DOI: 10.1021/acs.est.5b04050
|View full text |Cite
|
Sign up to set email alerts
|

Passive Sampling in Regulatory Chemical Monitoring of Nonpolar Organic Compounds in the Aquatic Environment

Abstract: We reviewed compliance monitoring requirements in the European Union, the United States, and the Oslo-Paris Convention for the protection of the marine environment of the North-East Atlantic, and evaluated if these are met by passive sampling methods for nonpolar compounds. The strengths and shortcomings of passive sampling are assessed for water, sediments, and biota. Passive water sampling is a suitable technique for measuring concentrations of freely dissolved compounds. This method yields results that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 137 publications
0
98
0
1
Order By: Relevance
“…In contrast to spot sampling, passive samplers allow to measure the more representative time weighted average water concentrations (TWA). Passive sampling data also provide information about the biologically available trace element fraction of the analysed water body (Booij et al, 2016). Besides the measurement of contaminant body burdens, the application of mussels as active sampling devices allows also the analysis of potential biological effects induced by the contaminants present in the surrounding water.…”
Section: Active and Passive Sampling Toolsmentioning
confidence: 99%
“…In contrast to spot sampling, passive samplers allow to measure the more representative time weighted average water concentrations (TWA). Passive sampling data also provide information about the biologically available trace element fraction of the analysed water body (Booij et al, 2016). Besides the measurement of contaminant body burdens, the application of mussels as active sampling devices allows also the analysis of potential biological effects induced by the contaminants present in the surrounding water.…”
Section: Active and Passive Sampling Toolsmentioning
confidence: 99%
“…Passive sampling in environmental applications has evolved from a scientific concept to a tool being promoted for use in regulatory decision making (Mayer et al 2003;Greenberg et al 2014;Booij et al 2016). During this evolution, several review articles have summarized the scientific foundations and approaches for passive sampling including its ability to estimate a chemical's freely dissolved concentration (C free ;Lohmann 2012;Lydy et al 2014;Mayer et al 2014;Ghosh et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although this issue was initially a matter of debate within analytical chemistry (Hawthorne et al 2000;Vaes et al 2000), experimental studies have now demonstrated that hydrophobic organic contaminants (such as polycyclic aromatic hydrocarbons [PAHs] and polychlorinated biphenyls) can be absorbed into various polymers, including silicone and low density polyethylene (LDPE) (Lohmann 2012). This process is the mechanistic basis for most passive sampling techniques for HOCs (Booij et al 2016). Recent tests with 7 different HOCs and 4 polymers showed that the sorption process depends strongly on the polymer type (H€ uffer and Hofmann 2016).…”
Section: Sorption and Desorption: The Influence Of Intrinsic And Extrmentioning
confidence: 99%